The inhibitive effect of vitamin B2, B6 and vitamin C on the cooper corrosion - Pranjoto Hartono; Anggorowati Adriana Anteng; Joewono Andrew; Suratno Lourentius; Candra Adi (E3S Web of Conferences, 2024)
Corrosion of copper (Cu) in sodium chloride (NaCl) and hydrochloric acid (HCl) can be inhibited by using inhibitors of vitamins B2, B6 and Vitamin C. The concentration of each vitamin varies between 400 – 1.100 ppm. The copper used is type Cu-OF/CW008A measuring 5 cm x 5 cm x 0.5 cm. The concentration of NaCl solution used as a corrosion medium is 30,000 ppm and 0.4 M HCl concentration. The corrosion process is carried out within 6 – 12 days. The calculation of the corrosion rate on Cu was carried out using the gravimetric method. The corrosion rate in acidic media (HCl) is greater than in neutral NaCl media. This phenomenon happens as the H+ ions in HCl acid is receptive to electrons from the oxidized Cu metal. The vitamin inhibitor layer on the surface of the Cu metal reduces the contact between the Cu metal and the corrosion medium, so that the interaction of H+ ions in the corrosion medium with the Cu surface is inhibited. Vitamin C can have multiple functions, at certain concentrations it can function as an inhibitor but if the concentration is enlarged it functions as an activator.